1993
DOI: 10.1213/00000539-199305000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Hemodilution Induces Stable Changes in Global Cardiovascular and Regional Myocardial Function

Abstract: The cardiovascular responses associated with isovolemic hemodilution have been described. However, the stability of these responses over time remains controversial. We hypothesized that the hemodynamic responses to isovolemic hemodilution are stable over time. Nine fentanyl-midazolam-anesthetized dogs were monitored to follow global cardiovascular and regional myocardial function. Isovolemic hemodilution was performed to a moderate (hemoglobin = 7.5 g%) target hemodilutional state that was maintained for 4 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
1
16
1
1
Order By: Relevance
“…In contrast to findings in chronic anemia states [24], [28], [29], the CI in homo-βthal mice rose further and reached a maximum at 10 months of age. Moreover, a persistent increase in LV mass and diameter demonstrate LV remodeling throughout life with progressive deterioration of the homo-βthal cardiac geometry/structure.…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast to findings in chronic anemia states [24], [28], [29], the CI in homo-βthal mice rose further and reached a maximum at 10 months of age. Moreover, a persistent increase in LV mass and diameter demonstrate LV remodeling throughout life with progressive deterioration of the homo-βthal cardiac geometry/structure.…”
Section: Discussioncontrasting
confidence: 96%
“…However, in previous studies in anesthetized dogs [3,34] elevated norepinephrine levels were already detected after less severe ANH to Hct levels between 19% and 21%. Furthermore the catecholamine-mediated hemodynamic changes following hemodilution could be partially blunted by β-receptor blockade [8,10,11], underlining the catecholaminergic influence during ANH.…”
Section: Discussionmentioning
confidence: 77%
“…5,6 Experiments designed to quantify the cardiovascular response to anemia have generally done so by the acute induction of severe anemia below 80 g/L. [7][8][9] Induced acute anemia is associated with a progressive increase in heart rate and cardiac output; 10,11 however, these changes are not found in patients with stable mild or moderate anemia. Studies involving adults with chronic anemia showed no consistent changes in cardiac output until hemoglobin levels fell below 70 g/L or 50% of normal.…”
Section: Anemia and Oxygen Deliverymentioning
confidence: 99%